828 Improved growth properties and immune surveillance in K-RAS G12V-transformed cells through overexpression of biglycan. (10th December 2020) - Subbarayan, Karthikeyan; Leisz, Sandra; Massa, Chiara; Balina, Sravankumar; Müller, Anja; Wickenhauser, Claudia; Seliger, Barbara
Abstract : Background: The extracellular matrix protein biglycan (BGN) plays an essential role in matrix assembly, cellular migration, adhesion, proliferation and apoptosis. Recently, BGN expression has been shown to be impaired upon HER-2/neu overexpression, which was associated with an up-regulation of MHC class I surface expression. However, there exists no information about the link between K-RAS-mediated immune escape and BGN expression. Methods: In vitro models of human K-RAS G12V transformed mouse fibroblasts and two human colorectal carcinoma (CRC) cell lines carrying a K-RAS G12V mutation (RKO and SW480) were used for the analysis of BGN expression by qPCR and Western blot. At the same time, the major histocompatibility complex (MHC) class I surface expression, as well as CD4+ and CD8+ cells, were determined by flow cytometry. The different K-RAS G12V cells and respective controls were stably transfected with BGN. Growth properties were analyzed by proliferation, migration and invasion assays. Luciferase reporter assays were used to determine the transcriptional regulation of MHC class I APM components. Tumorgenicity of BGN transfectants in comparison to control cells was evaluated by injection of respective transfectants s.c. into mice and tumor growth was monitored over time. Results: Both murine and human K-RAS G12V cells express low levels of BGN compared to control cells. Overexpression of BGN caused an inhibition of cell proliferation, a diminished anchorage-independent growth and a reduced migration rate. The altered in vitro growth properties of BGNhigh K-RAS G12V+ correlated with a delayed tumor growth and a reduced frequency of tumor formation in vivo. Restoration of BGN expression increased the expression of decorin as well as enhanced MHC class I expression in K-RAS G12V-transformed cells. This is due to a BGN-induced transcriptional upregulation of major components of the MHC class I antigen processing machinery (APM), such as the transporter associated with antigen processing TAP1, TAP2 and LMP2, in BGN transfectants of K-RAS G12V+ cells. The results were further supported by the fact that mice bearing tumors induced by BGNhigh K-RAS G12V+ cells showed a reduced MHC class I expression, which was associated with an enhanced frequency of CD8+ and CD4+ cells in the peripheral blood. Conclusions: Our data provide evidence that (i) proteoglycan signatures are modulated by K-RAS G12V transformation, (ii) loss of proteoglycan expression is directly or indirectly involved in immune escape of K-RAS G12V overexpressing tumor cells and (iii) BGN overexpression and enhanced basal decorin expression results in altered growth properties of K-RAS G12V cells. Thus, the reduced migration rate and restoration of MHC class I surface expression by BGN or other proteoglycans are important features for their anti-tumorigenic properties in K-RAS G12-transformed tumor cells including colorectal cancers. Acknowledgements: The project is supported by Wilhelm-Sander-Stiftung (No: 2019.076.1). Consent: Not applicable